Endothelial dysfunction in vascular complications of diabetes: a comprehensive review of mechanisms and implications - Yang, Dong-Rong; Wang, Meng-Yan; Zhang, Cheng-Lin; Wang, Yu (Frontiers in Endocrinology, 2024)
Diabetic vascular complications are prevalent and severe complications among diabetic patients, profoundly affecting both their quality of life and long-term prospects. These complications can be classified into macrovascular and microvascular complications. Under the impact of risk factors such as elevated blood glucose, blood pressure, and cholesterol lipids, the vascular endothelium undergoes endothelial dysfunction, characterized by increased inflammation and oxidative stress, decreased NO biosynthesis, endothelial-mesenchymal transition, senescence, and even cell death. These processes will ultimately lead to macrovascular diseases and microvascular diseases, with macrovascular diseases mainly characterized by atherosclerosis (AS) and microvascular diseases mainly characterized by thickening of the basement membrane. It further indicates a primary contributor to the elevated morbidity and mortality observed in individuals with diabetes. In this review, we will delve into the intricate mechanisms that drive endothelial dysfunction during diabetes progression and its associated vascular complications. Furthermore, we will outline various pharmacotherapies targeting diabetic endothelial dysfunction in the hope of accelerating effective therapeutic drug discovery for early control of diabetes and its vascular complications.